The Influence of Economic Intelligence on the Strategic Decision-Making Process: The Case of Entreprise Nationale des Industries Électroniques (ENIE) - Mokhtaria, BOUTIBA (Journal of Ecohumanism, 2026)
This study examines the impact of CI on the strategic decision-making process within ENIE. A quantitative survey was conducted among 35 employees, including managers and supervisors, using a structured questionnaire. The data were analyzed with SPSS v.26 and Smart PLS v.4 to test the model’s reliability and validate the research hypotheses.The results indicate a positive correlation between the adoption of CI practices (strategic intelligence, information protection, and influence) and the effectiveness of decisions at all stages. These findings confirm the central role of competitive intelligence as a strategic lever for enhancing organizational performance and competitiveness.